2001
DOI: 10.1002/mrd.1102
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sperm cryopreservation on sperm DNA stability and progeny development in rainbow trout

Abstract: This study was carried out to test how sperm cryopreservation affected nuclear DNA stability and whether progeny development was modified when eggs were fertilized with cryopreserved spermatozoa. The "comet assay" (alkaline single-cell gel electrophoresis assay) was adapted to trout spermatozoa to estimate DNA stability as measured by alkali-induced DNA strand break formation. Because trout eggs develop in water after fertilization (oviparous species) and that eggshell is easy to clear up after fixative treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
89
1
6

Year Published

2003
2003
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 166 publications
(102 citation statements)
references
References 40 publications
5
89
1
6
Order By: Relevance
“…Steel et al [2000] found no appreciable difference in the percentage of comet head DNA of fresh (81.7 AE 1.2%) and frozen-thawed (81.9 AE 2.8%) testicular sperm in contrast to recent studies that showed an increased percentage of DNA fragmentation in cryopreserved sperm samples from human [Donnelly et al 2001a[Donnelly et al , 2001bLabbe et al 2001;Thomson et al 2009]. Furthermore, results from equine [Linfor and Meyers 2002] and rhesus macaques [Li et al 2007] have revealed significantly higher sperm DNA damage in the absence of cryoprotectants prior to freezing.…”
Section: Discussionmentioning
confidence: 96%
“…Steel et al [2000] found no appreciable difference in the percentage of comet head DNA of fresh (81.7 AE 1.2%) and frozen-thawed (81.9 AE 2.8%) testicular sperm in contrast to recent studies that showed an increased percentage of DNA fragmentation in cryopreserved sperm samples from human [Donnelly et al 2001a[Donnelly et al , 2001bLabbe et al 2001;Thomson et al 2009]. Furthermore, results from equine [Linfor and Meyers 2002] and rhesus macaques [Li et al 2007] have revealed significantly higher sperm DNA damage in the absence of cryoprotectants prior to freezing.…”
Section: Discussionmentioning
confidence: 96%
“…These causes are many and range from environmental conditions such as cigarette smoking [99], irradiation [8], and chemotherapy [20,88] to pathophysiologic conditions such as leukocytospermia [5,35], varicoceles [105,107], and cancer [70]. Even iatrogenic causes such as sperm cryopreservation [32,73] have been associated with sperm DNA damage. Exact molecular mechanisms by which these conditions lead to sperm DNA damage and/or chromatin abnormalities are not fully understood, but there are currently three main theories which we will review: 1) chromatin packaging abnormalities, 2) reactive oxygen species, and 3) apoptosis.…”
Section: Etiologic Factorsmentioning
confidence: 99%
“…Some authors mention three possible factors which may cause DNA damage sperm during cryopreservation: i) direct damage of the sperm genome by the possible development of intracellular ice, which can act similarly to gamma radiation upon the DNA fragmentation (Miskolczi et al, 2005), ii) direct damage of the sperm genome by a type of oxygen reactant released by the dead cells or damaged during the freezing or thawing processes (Labbé et al, 2001) and, iii) induction of apoptotic processes on part of the cryopreservation (Cabrita et al, 2010). The factors (i) and (iii) possibly also involved in the damages to the sperm's plasmatic membrane.…”
Section: Discussionmentioning
confidence: 99%